2020
DOI: 10.3389/fpsyt.2020.586083
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and the Interplay Between Telomeres and Mitochondria in Bipolar Disorder

Abstract: Bipolar disorder is a severe psychiatric disorder which affects more than 1% of the world’s population and is a leading cause of disability among young people. For the past 50 years, lithium has been the drug of choice for maintenance treatment of bipolar disorder due to its potent ability to prevent both manic and depressive episodes as well as suicide. However, though lithium has been associated with a multitude of effects within different cellular pathways and biological systems, its specific mechanism of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 195 publications
0
17
0
Order By: Relevance
“…Short-term lithium treatment has been shown to lower SOD:CAT and TBARS levels in patients with BD who were experiencing mania as well [95]. These outcomes were corroborated by a follow-up study showing a reduction in SOD and TBARS levels in patients with BD after 6 weeks of lithium therapy [285]. The study also found that lithium responders exhibited significantly lower TBARS levels compared with nonresponders [106].…”
Section: Lithium Therapymentioning
confidence: 71%
“…Short-term lithium treatment has been shown to lower SOD:CAT and TBARS levels in patients with BD who were experiencing mania as well [95]. These outcomes were corroborated by a follow-up study showing a reduction in SOD and TBARS levels in patients with BD after 6 weeks of lithium therapy [285]. The study also found that lithium responders exhibited significantly lower TBARS levels compared with nonresponders [106].…”
Section: Lithium Therapymentioning
confidence: 71%
“…Findings from these studies expand our knowledge on the mechanism of action of lithium, also supporting hypotheses that were generated through different strategies by earlier studies. This is for instance the case of mitochondria [104]. Indeed, a recent study explored the effect of in vitro treatment with lithium on oxygen consumption rate (OCR) and glycolytic rate (two indexes of mitochondrial respiratory function) in iPSC derived neural precursor cells (NPCs) [105].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found, in exploratory analyses, that patients within the depressed group treated with mood stabilizers had the lowest levels of ccf-mtDNA, suggesting that at least part of the between-group differences in ccf-mtDNA may be accounted for by medication status. Psychotropic medications, and lithium in particular, are known to influence mitochondrial biology and cellular health [ 20 ]. In one study based on pluripotent stem cell technology, mitochondrial abnormalities were found in neurons from patients with bipolar disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of psychotropic medications may influence mitochondrial function and cellular health [13][14][15]. For instance, preclinical studies have shown that SSRIs, antipsychotics, and mood stabilizers may improve cellular health and have neuroprotective effects [16][17][18][19][20][21], but the relationship between these medications and cellular stress marker ccf-mtDNA has not yet been investigated in a real-life clinical sample of depression. Moreover, no previous studies that have investigated the relationship between ccf-mtDNA and specific symptom profiles of depression.…”
Section: Introductionmentioning
confidence: 99%